Prevalence of supplement usage and related attitudes and reasons among fitness athletes in the gyms of Kashan and its relationship with feeding behavior: a cross-sectional study - Fatemeh Moradi; Akram Yazdani; Faezeh Nematolahi; Seyed Mohammad Hosseini-Roknabadi; Nasrin Sharifi (BMC, 2024)
Abstract Background The overuse of supplements among athletes is a widespread issue affecting the health of both male and female athletes. However, research on supplements usage among female fitness athletes is limited, and there is little information on the feeding behavior of fitness athletes who use supplements. This study aimed to fill the gap in knowledge by examining the prevalence of supplement usage and its related attitudes and reasons among fitness athletes in the gyms of Kashan. It further aimed to investigate the correlation between supplements usage and the feeding behavior of fitness athletes. Methods For these purposes, in this cross-sectional study, 433 fitness athletes (15‒46 years old) in 28 gyms in the city of Kashan were surveyed using a researcher-made questionnaire in 2023. Five experts confirmed the validity of the questionnaire. The present study considered the supplements based on the Australian Institute of Sport position statement. A Chi-square analysis was conducted to examine the relationship between the study variables and supplement usage. Results Overall, 272 male and 161 female fitness athletes participated in this study. The results revealed that 57.9% of participants used supplements, most commonly vitamin C, vitamin D, omega-3 fatty acids, and whey protein. The main reason for using supplements was to speed up body repair after exercise (69.5%). Additionally, 41.8% of these athletes believed that using supplements improves their overall performance, and 21.9% thought that supplements do not harm the body. Moreover, a correlation was observed between feeding behavior and the consumption of supplements. It was found that athletes who use supplements tend to eat more white meat, seeds, and nuts and fewer high-fat dairy products than those who do not consume them. Conclusion Using supplements among fitness athletes in the gyms of Kashan is common. The main reason for using these substances was to speed up body repair after exercise, and nearly half of the athletes believed that supplements improved their performance. In addition, it was revealed that athletes who take supplements have healthier feeding behaviors than those who do not. Thus, these findings confirm the necessity of informing fitness athletes about using supplements.